Analysis of Students’ Learning Difficulties in English for Counseling Guidance Department at Muhammadiyah University of Enrekang - Atiqa, Nur; Mustakim, Mustakim; Hasan, Hasan; Balkis, Ratu (Maspul Journal of English Studies, 2022)
The purpose of this study is to examine the factors influencing the students' learning difficulties at Muhammadiyah University of Enrekang as well as their problems learning English. This research is qualitative by collecting information from thirty students in the counseling guidance study program. The outcome of this assessment, which employed a descriptive methodology, revealed that speaking skills were the area in which students had the most trouble learning. Students' lack of self-confidence, lack of motivation, lack of speaking ability, difficulty memorizing vocabulary, lack of listening ability, lack of practicing pronunciation, lack of understanding the material, lack of practice partner, learning media, lack of writing ability, lack of reading ability, translating, feeling that learning English is not important, and lack of having a practice partner are the factors that make learning English difficult for students.